2022
DOI: 10.3390/ijerph19159468
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Functioning and the Educational Experiences of Students with ASD during the COVID-19 Pandemic in Poland

Abstract: Due to their individual developmental and learning needs, adolescents with autism spectrum disorder (ASD) benefit from a variety of educational, medical, and therapeutic services. During the COVID-19 pandemic, these services were discontinued or significantly reduced, which may have resulted in increased difficulties in coping with various areas of life. The purpose of this study was to explore how the pandemic affected the psychosocial and educational functioning of students with ASD. A qualitative, problem-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…Multiple traumatic events in our patient's history, including sports failure and COVID-19 school closures, preceded the onset of depressive symptoms, and disrupted her routine, highlighting the impact of trauma and COVID-19 pandemic in depression development in ASD samples, as evidenced in previous studies and reports (26,(50)(51)(52). Also, COVID-19 lockdown may have exacerbated maladaptive coping strategies, such as ruminations on past traumatic experiences.…”
Section: Discussionsupporting
confidence: 62%
“…Multiple traumatic events in our patient's history, including sports failure and COVID-19 school closures, preceded the onset of depressive symptoms, and disrupted her routine, highlighting the impact of trauma and COVID-19 pandemic in depression development in ASD samples, as evidenced in previous studies and reports (26,(50)(51)(52). Also, COVID-19 lockdown may have exacerbated maladaptive coping strategies, such as ruminations on past traumatic experiences.…”
Section: Discussionsupporting
confidence: 62%
“…Studies have shown that parents of autistic children experienced even higher levels of psychological stress during the pandemic ( 34 ) and that this stress profoundly impacted their expectations of and planning for their children’s education ( 35 , 36 ). As we move into the post-pandemic era, exploring the relationship between psychological stress and views of school success is of great academic interest.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding loneliness is important due to its relationship to the mental and physical health of the individual. Researchers show that social isolation and feelings of loneliness lead to feelings of constant stress and depression, and also trigger physiological changes, linked to the immune system and inflammatory responses, that can further exacerbate health [19,26,27]. As a result of a persistent sense of loneliness, susceptibility to mental disorders and psychosomatic diseases may also increase [28].…”
Section: Introductionmentioning
confidence: 99%